2019
DOI: 10.1123/japa.2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Peer Experience for Older People Encouraging Other Older People to Engage in Resistance Training: A Qualitative Study

Abstract: Resistance training (RT) can maintain and improve physical and mental health in older adults, but this population has low levels of RT participation. Linking older people participating in RT (i.e., peers) with those who have not may promote and maintain adherence. This qualitative study explored the experience of peers in encouraging RT participation among older adults. Data were collected using focus groups, researcher observations, and semistructured interviews. Thematic analysis was conducted. Older people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Peer volunteers were deemed to be important motivators and enhanced single instructor-led sessions by providing additional support (as also noted elsewhere [ 15 19 , 21 ]). One reason for peer-support implementation is that attendees can develop a positive shared experience with their peers, staff, and volunteers [ 18 , 21 , 23 , 24 ]. Participants in the current study noted that high levels of optimism, compassion and the friendly nature shown by both the peer-support volunteers and the qualified instructor fostered increased interaction and social inclusion across the groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peer volunteers were deemed to be important motivators and enhanced single instructor-led sessions by providing additional support (as also noted elsewhere [ 15 19 , 21 ]). One reason for peer-support implementation is that attendees can develop a positive shared experience with their peers, staff, and volunteers [ 18 , 21 , 23 , 24 ]. Participants in the current study noted that high levels of optimism, compassion and the friendly nature shown by both the peer-support volunteers and the qualified instructor fostered increased interaction and social inclusion across the groups [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [ 22 ] shows the adoption of a motivational role by peer support workers improves self-efficacy, perceptions of confidence and self-determination within participants. Face-to-face and two-way communication between peers and service users has led to mutually positive relationships through increased honestly, empathy and transparency [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…older people with knowledge and experience in the area of interest) have been linked to a person or people who have limited experience or knowledge in an area, particularly health. The aim of linking a novice with a peer is to provide an atmosphere where like-minded people can work together to improve the experience for the novice, while the peer gains benefits too, usually in helping and empowering others (Watkins, Burton, & Hill, 2019).…”
Section: Peers and Strength Training: Pilot Rctmentioning
confidence: 99%